STUDENT RESEARCH IN ENGLISH LANGUAGE LEARNING - Angelianawati, L. (Jurnal Dinamika Pendidikan, 2015)
English Language Teaching (ELT) is in need of innovative and up-to-date teaching strategies which can develop studentsâ language competence and performance effectively. Student research is affirmed as one of effective as well as innovative teaching strategies, which develops student-centered learning. Through this strategy, the students learn how gathering information, interpreting it, and making conclusions based on the information gathered. The main purpose of applying this strategy is to make the students learn from the research, discover and also construct knowledge by themselves, as well as use the language. One important point that should be considered in implementing this strategy is the level of education in which the strategy is implemented. This article presents the way how this strategy may be utilized in the classroom.Keywords : student research, teaching strategy, student centered learning